The Effect of Problem Based Learning (PBL) Learning Models on Student Chemistry Learning Outcomes in Buffer Solution Material - Limbong, Rachel Wandira; Silaban, Saronom (Universitas Lampung, 2023)
Abstract:The Effect Of Problem-Based Learning (PBL) Learning Model On Students’ Learning Outcomes In Buffer Solution Materials . This study aims to: 1) Change the effect of the Problem Based Learning learning model on learning outcomes of material buffers in class XI MIPA and 2) find out which cognitive domain is the most developed Problem Based Learning learning model in the application of buffer solutions. Samples were taken randomly as many as 32 students in class XI MIPA SMA Negeri 5 Medan. The instrument used in this study is a test instrument. The ice instrument was carried out 2 times, namely pre-test and post-test. The instrument used was an objective test with a total of 30 questions to test the level of students' cognitive abilities, namely C₁ (knowledge), C₂ (understanding), and C4 (analysis). PBL results show that there is an increase in test scores. Where the average pretest score is only 62.94 while the average post test score is 80.42. Based on this, learning using the Problem Based Learning model is able to increase knowledge of the buffer solution material in class XI MIPA students at SMA Negeri 5 Medan.Keywords: Problem Based Learning (PBL), Buffer Solutions, Chemistry Skills DOI: 10.23960/jppk.v12.i3.2023.05